2014
DOI: 10.1093/toxsci/kfu142
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Strain Less Responsive to Dioxin-Induced Prostaglandin E2 Synthesis Is Resistant to the Onset of Neonatal Hydronephrosis

Abstract: Dioxin is a ubiquitous environmental pollutant that induces toxicity when bound to the aryl hydrocarbon receptor (AhR). Significant differences in susceptibility of mouse strains to dioxin toxicity are largely accounted for by the dissociation constant of binding to dioxins of AhR subtypes encoded by different alleles. We showed that cyclooxygenase-2 (COX-2) and microsomal prostaglandin E synthase-1 (mPGES-1), components of a prostanoid synthesis pathway, play essential roles in the onset of 2,3,7,8-tetrachlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
1
5
1
Order By: Relevance
“…We showed that IUL TCDD exposure, followed by adult T þ E 2 treatment, increased kidney wet weight and incidence of frank hydronephrosis. It should be noted that others have demonstrated IUL TCDD exposure induces upper urinary tract dysfunction including fetal hydronephrosis (Aida-Yasuoka et al, 2014;Moore et al, 1973). We did not observe frank hydronephrosis in mice exposed to TCDD without adult exogenous hormone exposure.…”
Section: Discussioncontrasting
confidence: 51%
“…We showed that IUL TCDD exposure, followed by adult T þ E 2 treatment, increased kidney wet weight and incidence of frank hydronephrosis. It should be noted that others have demonstrated IUL TCDD exposure induces upper urinary tract dysfunction including fetal hydronephrosis (Aida-Yasuoka et al, 2014;Moore et al, 1973). We did not observe frank hydronephrosis in mice exposed to TCDD without adult exogenous hormone exposure.…”
Section: Discussioncontrasting
confidence: 51%
“…The role of AQP2 in the onset of hydronephrosis is not clear because there are some inconsistent observations on the abundance of AQP2 and its localization in the different experiments, such as pharmacological inhibition of V2R (5), nonsense mutation of V2R (58), and our present ( Fig. 4) and previous studies (2,35,55). Studies on short-term regulation and long-term adaptation of apical-trafficking, endocytosis, and expression of AQP2 may elucidate the underlying mechanism.…”
Section: F757mentioning
confidence: 51%
“…4, C and F) (2), resulting in a decrease in water permeability at the collecting duct (17,34) to produce dilute urine (Fig. 4A) (2). Hydronephrosis accompanied with polyuria and low urine osmolality has been reported in another mouse model of a disrupted renal AVP system (58), in which renal V2 vasopressin receptor (V2R) is genetically ablated by a nonsense mutation.…”
Section: F757mentioning
confidence: 95%
“…Signaling downstream of PGE 2 leading to TiNH remains to be elucidated. A plausible mechanism is that increased PGE 2 in the renal tubules interferes with the water reabsorption system [59,60,61], resulting in a decrease in water permeability [60,61] to produce diluted urine [46,62]; consequently, the increased urine volume [46] overwhelms the ureter propelling capacity and causes backpressure in the kidney pelvicalyceal space.…”
Section: Hydronephrosismentioning
confidence: 99%
“…Little is known about additional factors determining sensitivity to TCDD toxicity. C57BL/6J and BALB/cA mice exhibit a substantial difference in the sensitivity to TiNH, although both strains possess AhRs with high affinity to TCDD [62]. This difference is attributed to the lower responsiveness of mPGES-1 expression to TCDD exposure in the kidney of BALB/cA pups.…”
Section: Hydronephrosismentioning
confidence: 99%